Redescription of the freshwater shrimp Macrobrachium jelskii (Miers, 1877) (Caridea, Palaemonidae) - Vera-Silva, Ana Luiza; Carvalho, Fabrício Lopes; Mantelatto, Fernando Luis (Zootaxa, 2017)
Macrobrachium jelskii is a freshwater shrimp endemic to South America, occurring in all major Brazilian basins. It is used in various activities, such as fishing, fishkeeping and even as food for humans and animals, and therefore its distribution is affected by anthropic influence. Misidentification of M. jelskii is recurrent because of its morphological similarity to some sympatric species such as M. amazonicum and M. acanthurus. Thus, the aim of this study is to redescribe M. jelskii, proposing some characteristics that allow for a clearer differentiation of this species when compared to other similar congeneric species that occur in South America. The informative characters were the size and the shape of the rostrum, the ratio of the carpus and chela, the ratio of the chela and carapace length and the shape of the carpus of the second pereiopod, as well as the ratio between the length of the internal pair of posterior spine of telson and median apex of the posterior margin of telson. Although the intraspecific variability is high, the combination of the characters mentioned herein, including a morphological key, is very useful and makes it easier to differentiate between these three species.